Caries Experience and Oral Hygiene Status of a Group of Visually Impaired Children in Istanbul, Turkey - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
Purpose: To evaluate the caries experience, oral hygiene status and oral health knowledge of a group of visually impaired students. Materials and Methods: The study was conducted at one of the largest visually impaired children's schools among students aged between 7 and 16 years (n = 178) in Istanbul, Turkey. A 16-item questionnaire was asked in addition to a clinical tooth examination. The 16-item verbal questionnaire was developed to record the students' general health, impairment, the socioeconomic profile and education level of their parents, oral health knowledge, sources of information about oral health and oral hygiene habits. Oral hygiene was assessed according to Greene and Vermillion's Simplified Oral Hygiene Index (OHI-S). To measure the oral hygiene status, OHI-S index scores were recorded. Additionally, DMFT and dft indices were documented. Results: Only 26.40% of children were caries free, and only 2.2% of students had good oral hygiene. A total of 3.3% of these students were mildly retarded and 2.8% of them had a developmental disability. Visually impaired children exhibited a fair-to-poor level of oral hygiene. Conclusion: Maintenance of oral hygiene remains the greatest challenge in the care of visually impaired children.
Keywords: caries experience; oral health knowledge; oral hygiene; visually impaired children; TURKISH CHILDREN; BLIND